2024
DOI: 10.3389/fbioe.2024.1345163
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral nerve injury repair by electrical stimulation combined with graphene-based scaffolds

Yuanyuan Zhao,
Yang Liu,
Shiqi Kang
et al.

Abstract: Peripheral nerve injury (PNI) is a common clinical problem, which due to poor recovery often leads to limb dysfunction and sensory abnormalities in patients. Tissue-engineered nerve guidance conduits (NGCs) that are designed and fabricated from different materials are the potential alternative to nerve autografts. However, translation of these NGCs from lab to commercial scale has not been well achieved. Complete functional recovery with the aid of NGCs in PNI becomes a topic of general interest in tissue engi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 108 publications
0
1
0
Order By: Relevance
“…In addition, graphene has excellent electrical conductivity, and its prepared materials have bioelectrical activity that is conducive to signal transmission. Therefore, it is regarded as an ideal scaffold material in the field of neural tissue engineering ( Zhao et al, 2024a ). Increasingly, studies have confirmed the significant potential of graphene nanotechnology in repairing peripheral nerves ( Grijalvo and Díaz, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, graphene has excellent electrical conductivity, and its prepared materials have bioelectrical activity that is conducive to signal transmission. Therefore, it is regarded as an ideal scaffold material in the field of neural tissue engineering ( Zhao et al, 2024a ). Increasingly, studies have confirmed the significant potential of graphene nanotechnology in repairing peripheral nerves ( Grijalvo and Díaz, 2021 ).…”
Section: Introductionmentioning
confidence: 99%